Etiopathogenesis of psoriasis [Psoriasisin etyopatogenezi] - (:unkn) unknown (My University, 2008)
Psoriasis is a common chronic inflammatory disease affecting the skin, joints and also having association with metabolic syndrome and coronary artery disease. Although recent progress has helped in elucidating the immunologic pathways and genetic basis of the disease, the etiology remains unknown. This review focuses on the role of cells involved in pathogenesis; T-lymphocytes, dendritic cell subgroups, macrophages, neutrophils, mast cells and keratinocytes and summarizes the immunopathogenesis.
Keywords: IL 12/23; Immunopathogenesis; Psoriasis